The caloric and sugar content of beverages purchased at different store-types changed after the sugary drinks taxation in Mexico - Lilia S. Pedraza; Barry M. Popkin; Carolina Batis; Linda Adair; Whitney R. Robinson; David K. Guilkey; Lindsey Smith Taillie (BMC, 2019)
Abstract Background Following the 2014 sugary drinks tax implementation in Mexico, promising reduction in the volume of purchases of taxed beverages were observed overall and at different store-types. However, the tax's effects on purchasing patterns of calories and sugar remain unclear. Methods Using longitudinal data from Mexican households (n = 7038), we examined changes in volume, calories and total sugar of packaged beverages purchased from 2012 to 2016 overall and by store-type. We used fixed effects models to estimate means for volume, calories, and sugar of households. To address the potential selectivity from households shopping at different stores, we calculated inverse probability weights to model the purchases changes over time by store-type. Results For taxed beverages, the volume of purchases declined by − 49 ml and -30 ml in the first year and second year post tax (2014 and 2015, respectively), while purchases leveled off in the third year of the tax (2016). Calories and sugar from taxed beverage purchases decreased over time, with the majority of the declines occurring in the first two years post-tax implementation. The volume of untaxed beverage purchases increased, whereas changes in calories and total sugar of untaxed beverages were minimal. Store level purchases of taxed beverages significantly decreased in the first two years post taxation (2014 and to 2015) only in supermarkets and traditional stores. The steepest declines in purchases of taxed beverages in 2014 were observed at supermarkets (− 40 ml or − 45%). The volume of purchases of untaxed beverages increased over time in almost all store-types, while calories and sugar minimally decreased over time. Conclusion Although the Mexican tax on SSBs has lowered the purchases of sugary drinks 3 years after the tax implementation, the tax should be strengthened and store-specific interventions should be implemented to further reduce SSBs purchases in the Mexican population.